Model Tempat Sampah Braille dengan Sensor Suara terhadap Ketepatan Memilah Sampah Siswa Tunanetra di SLB Negeri I Bantul - Rizki Kurniawan Saputra; Siti Hani Istiqomah; Achmad Husein (Poltekkes Kemenkes Yogyakarta, 2018)
Waste management in schools is an effort to make schools comfortable, healthy, and clean; included in special schools. Waste bin with Braille letter and equipped with voice sensor is designed to stimulate and to assist blind students in separating waste accurately by their types withthe help of audio stimulation. The purpose of this study was to determine the utilization of thisinnovative waste bin on students’ accuracy in waste sorting. This study was an experiment withpost-test only control group design, and was taken place in the State Special School I of Bantul,and all students of blind department as the respondent. Because the data obtained did not fulfilled the normality distribution assumption, Man Whitney non-parametric test was used in theanalysis, and the results showed that the brailled and voice sensored waste bin is proven affecting (p=0,011) the students’ accuracy on waste separation according to their types (i.e. plastic,paper, and food scraps).